2016
DOI: 10.3906/biy-1505-29
|View full text |Cite
|
Sign up to set email alerts
|

Mucus of Achatina fulica stimulates mineralization and inflammatoryresponse in dental pulp cells

Abstract: IntroductionDental and oral diseases are major concerns in Thailand, affecting the country's health system. Everyone, at any age, is at risk of losing teeth. Tooth loss can lead to many health problems, including difficulty chewing, which increases the risk of poor nutrition. In addition, tooth loss leaves a large gap, leading to plaque accumulation that can cause periodontal disease. Moreover, the remaining teeth start to shift in an attempt to fill in the gap, leading to misalignment of teeth. Losing teeth m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 38 publications
1
20
0
2
Order By: Relevance
“…Primary PDL cells and APCs were obtained as previously reported. 21 Caries-free third molar that was extracted for orthodontic treatment purposes was used. PDL cells were derived from 2 different donors (N1 and N2).…”
Section: Methodsmentioning
confidence: 99%
“…Primary PDL cells and APCs were obtained as previously reported. 21 Caries-free third molar that was extracted for orthodontic treatment purposes was used. PDL cells were derived from 2 different donors (N1 and N2).…”
Section: Methodsmentioning
confidence: 99%
“…Mucus of A. fulica was prepared as previously described [9]. Briefly, the snail mucus samples were collected from adult A. fulica by mild intermittent irritation in an ultrasonicating bath for 5 rounds of 15 sec at 30°C.…”
Section: Preparation Of Snail Mucusmentioning
confidence: 99%
“…A previous study, by Harti et al, found that a combination of A. fulica mucus and chitosan (at a ratio of 1:2) was effective in wound healing in mice [8]. Recently, Kantawong et al (2016) demonstrated that A. fulica mucus enhanced mineralization in dental pulp cells (DPCs) [9]. Although, the DPCs contained mesenchymal stem cell population, the major population were fibroblasts which also responded to the induction so the expressions of OPN and OCN were slightly increased.…”
Section: Introductionmentioning
confidence: 99%
“…Another study evidenced that snail mucus can be used, potentially, in regenerating and repairing bone and teeth, because it increased the expression of osteopontin and NF-κB and induced the expression of some inflammatory genes in dental pulp cells [21].…”
Section: Composition Of Snail Mucusmentioning
confidence: 99%